Analyzing the Impact of E-Health Implementation on Service Quality through Technology Literacy at Bangkingan Community Health Center: A Structural Equation Modeling Approach - Rachmawati, Tri Indah; Ronny, Ronny; Setia, Shinta (Universitas Muhammadiyah Pontianak, 2025)
This study analyzes the effect of e-health implementation on service quality mediated by technology literacy at Bangkingan Public Health Center using Structural Equation Modeling (SEM). The results show that e-health adoption has a significant positive impact on technology literacy and service quality, with technology literacy partially mediating the relationship. These findings highlight the need for improved training and digital infrastructure to enhance responsiveness and empathy in healthcare services, supporting sustainable e-health implementation in primary care.